Learning Process as a Driving Force for Policy Implementation on Participatory Development of Pre-school Child Center Prototype: Non Thai District Case Study, Nakhon Ratchasima Province - Singtipphun, Chalermsri (Journal of Health Science of Thailand, 2018)
Nakhon Ratchasima Health Provincial Office, the local government organizations and academic centers saw significantly local integration of development, model and conceptual adjustment of relevant parties at all levels. They agreed to join for pre-school child center developing prototype, management of processing and management of learning process for concerning parties. As such, selected child learning center model (Non Thai district case study : Ratchasima Province) was selected and aimed to develop the learning process as a driving mechanism for the policy. The participatory prototype child development center : Non Thai district Nakhon Ratchasima case study, 2007 was a qualitative research. The study was conducted from May to September 2007. There were 32 districts and 529 child centers in Nakhon Ratchasima province. On voluntary basis, Nonthai district was selected. The district had 20 child centers transferred from all sectors: 6 centres from the Community Development, 2 centres Department of religion, 3 centres the Officer of National Primary Education and 9 centres self establishment. Data collection was made in indepth interviews and focus group discussions. Key informants were 1 sheriff, 2 mayors, 2 local government officials, 3 local government organizations members, 1 public health district, 5 public health officers, 1 child care authority and 5 parents. Content analysis with thematic analysis and data monitoring by triangulation were employed. The results showed that the child carers played a key role in community development of child centers. They should be knowledge able, understanding, having capacity and skills to treat preschool children. In addition, adequate support by the executive, party leaders and local networks were required in any operation. The child development centers should be operated in an integrated manner. In that connection all sectors were involved in defining problems, joint planning, policy making, operational guide lines and area management resulting in intense awareness in the community. They should have been proactive to adapt, jointly analyse, systematically plan for upcoming changes in a thrive to accommodate volatile situations. They should enhance the learning process for database development leading to community-based public policy. The suggestion was that the operation model of participatory development of child model center in the community should be replicated in other areas apart from Nakhon Ratchasima. Committee and working group child development center should be established. The agencies included the local administrative organizations, provincial agencies, district agencies and that their clear roles was defined to create effective coordination system.